Long-term survival with a combination of immunotherapy, anti-angiogenesis, and traditional radiotherapy in brain metastatic small cell lung cancer: a case report - Long, Yan-yan; Chen, Jing; Xie, Yue; Wang, Ying; Wu, Yong-zhong; Xv, Ying; Weng, Ke-gui; Zhou, Wei (Frontiers in Oncology, 2023)
Purpose Brain metastases (BMs) are common in Small Cell Lung Cancer (SCLC), but the prognosis is very poor. Currently, there is no standard of care on what constitutes optimal treatment, and there is no consensus regarding maintenance therapy in SCLC. Case description We report the case of a 55-year-old man with advanced SCLC. After the initial diagnosis, he received routine chemotherapy and chest radiotherapy but developed brain metastases with 2 lesions seven months later. We used an effective combination therapy consisting of the antiangiogenic inhibitor, Anlotinib and whole-brain radiotherapy. We then administered anti-PD-L1 immunotherapy Atezolizumab in combination with Anlotinib as long-term maintenance therapy. Twelve months later, there was a progression in one of the brain metastases. The patient underwent further stereotactic radiotherapy (SRT) for the lesion. However, after four months of treatment with SRT, the lesion began to gradually grow in size. The patient underwent surgical resection of the lesion, which confirmed radioactive brain necrosis. After a full 3-year course of anti-PD-L1 therapy, the patient discontinued immunotherapy and was administered only Anlotinib as maintenance. At the time of writing up this report, the patient was alive and the overall survival reached 41 months after the onset of BM. Conclusion This indicated a potential synergistic effect of combined immunotherapy and antiangiogenic targeted therapy with local radiotherapy in patients with BM-SCLC and can provide directions for future clinical decisions.